The Case of Inferred Doability: An Analysis of the Socio-institutional Background of the STAP Cell Scandal. Issue 2 (1st June 2018) - Mikami, Koichi
Abstract: On 28 January 2014, Haruko Obokata and her colleagues held a press conference regarding their new method of producing stem cells. The cells, named STAP (stimulus-triggered acquisition of pluripotency) cells, were of considerable interest not only for stem cell scientists but also for the wider society in Japan because both its government and citizens enjoyed the international reputation earned for the country by Shinya Yamanaka's earlier success in developing a novel technique of cell reprogramming. However, it was soon pointed out that the data in the research article seemed fabricated and was hence suggested that their claims lacked scientific credibility. What was initially considered another triumph of Japanese stem cell research thus resulted in a major national scandal. Instead of seeing this case merely as one of scientific misconduct, this article examines it as a window into the local culture of stem cell research and argues that the socio-institutional background of Obokata's work incited the researchers involved to infer doability of STAP cell research. The problem with this inference surfaced after those who did not share the culture challenged the robustness of her work, suggesting some cultures of science may be more vulnerable to scientific misconduct than others.